Summary of the Proceedings of the Fourth International Economics Seminar: World Bank, Washington, DC 13-14 Dhu al Qa'dah 1412/ 16-17 May 1992 (American Journal of Islam and Society, 1992)
The theme of the Fourth International Islamic Economics Seminarwas "Economic Growth and Human Resource Development in an IslamicPerspective." It was a joint undertaking of the Association of Muslim SocialScientists (AMSS) and the International Institute of Islamic Thought(IIIT). The program was divided into five sessions: a) Human ResourceDevelopment in an Islamic Perspective; b) Human Resource Developmentin a Comparative Perspective; c) Issues in Human Resource Development:Case Studies from Selected Muslim Countries; d) Human Resources, EconomicDevelopment, and Government Policies in Muslim Countries; ande) Business Sector and Human Resource Development. This latter sessionalso dealt with the role of financial institutions in human developmentfrom an Islamic perspective. Welcoming and opening remarks were madeby Sultan Ahmad of the World Bank and Sayyid Syeed of the AMSS ...